From Marginalization to Recognition: The Impact of Islamic Political Economy on Indonesia's Islamic Economy During the New Order - Hamid, Ahmad Munir; Fitrianto, Achmad Room; Ahmed, Ishfaq (Economica: Jurnal Ekonomi Islam, 2024)
The New Order era (1966–1998) marks a pivotal period in Indonesia's political and economic history. This study examines the influence of Islamic political economy on the evolution of Islamic economy during this time, using a literature review to explore how political dynamics and economic policies shaped its development. The findings reveal that Islamic political economy faced significant challenges due to the New Order government's focus on capitalist and industrial-oriented policies, which often marginalized sharia-based economic systems. For instance, the Islamic banking sector struggled to expand as regulations were more favorable to conventional banks. Despite these obstacles, intellectual groups and scholars sought to integrate Islamic principles into national policies, with the establishment of Islamic financial institutions like Bank Muamalat Indonesia in 1991 serving as a milestone. By the end of the New Order era, there was a noticeable increase in public interest and awareness of Islamic economy, driven by political shifts and a growing desire for a fairer, Islamic-aligned economic system. Consequently, Islamic economics began to gain wider recognition, eventually becoming an integral part of the national economic framework.